Inadequate oxygen delivery index dose is associated with cardiac arrest risk in neonates following cardiopulmonary bypass surgery. (September 2019) - Futterman, Craig; Salvin, Joshua W.; McManus, Michael; Lowry, Adam W.; Baronov, Dimitar; Almodovar, Melvin C.; Pineda, Jose A.; Nadkarni, Vinay M.; Laussen, Peter C.; Gazit, Avihu Z.
Abstract: Aim: To evaluate the Inadequate oxygen delivery (IDO2 ) index dose as a predictor of cardiac arrest (CA) in neonates following congenital heart surgery. Methods: Retrospective cohort study in 3 US pediatric cardiac intensive units (1/2011- 8/2016). Calculated IDO2 index values were blinded to bedside clinicians and generated from data collected up to 30 days postoperatively, or until death or ECMO initiation. Control event data was collected from patients who did not experience CA or require ECMO. IDO2 dose was computed over a 120-min window up to 30 min prior to the CA and control events. A multivariate logistic regression prediction model including the IDO2 dose and presence or absence of a single ventricle (SV) was used. Model performance metrics were the odds ratio for each regression coefficient and receiver operating characteristic area under the curve (ROC AUC). Results: Of 897 patients monitored during the study period, 601 met inclusion criteria: 29 patients had CA (33 events) and 572 patients were used for control events. Seventeen (59%) CA and 125 (26%) control events occurred in SV patients. Median age/weight at surgery and level of monitoring were similar in both groups. Median postoperative event time was 0.73 days [0.05–22.39] in CA patients and 0.82 days [0.08 25.11] in control patients. Odds ratio of the IDO2 dose coefficient was 1.008 (95% CI: 1.006–1.012, p = 0.0445), and 2.952 (95% CI: 2.952–3.258, p = 0.0079) in SV. The ROC AUC using both coefficients was 0.74 (95% CI: 0.73–0.75). These associations of IDO2 dose with CA risk remained robust, even when censored periods prior to arrest were 10 and 20 min. Conclusion: In neonates post-CPB surgery, higher IDO2 index dose over a 120-min monitoring period is associated with increased risk of cardiac arrest, even when censoring data 10, 20 or 30 min prior to the CA event.